2023
DOI: 10.1101/2023.10.26.23297597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complement dysregulation is a predictive and therapeutically amenable feature of long COVID

Kirsten Baillie,
Helen E Davies,
Samuel B K Keat
et al.

Abstract: Background: Long COVID encompasses a heterogeneous set of ongoing symptoms that affect many individuals after recovery from infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The underlying biological mechanisms nonetheless remain obscure, precluding accurate diagnosis and effective intervention. Complement dysregulation is a hallmark of acute COVID-19 but has not been investigated as a potential determinant of long COVID. Methods: We quantified a series of complement proteins, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…5) contrasting observations from the acute phase 68,69 (Table 1). The complement system is also known for a complex relationship with long COVID 70 : complement dysregulation might even be predictive of long COVID 71 . The complement cascade directly associates with altered blood coagulation in COVID-19 pathology 20,72,73 , and blood coagulation, which in turn involves platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…5) contrasting observations from the acute phase 68,69 (Table 1). The complement system is also known for a complex relationship with long COVID 70 : complement dysregulation might even be predictive of long COVID 71 . The complement cascade directly associates with altered blood coagulation in COVID-19 pathology 20,72,73 , and blood coagulation, which in turn involves platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…A complex interplay exists between increased Another hypothesis would be complement activation in a severe SARS-CoV-2 infection. In this sense, the chronic or persistent inflammatory response associated with the deregulation of the complement system, microthrombosis phenomena, and endothelial dysfunction [128] could trigger various manifestations in LC, according to some recent studies in which they were identified as reliable biomarkers (fractions Ba, iC3b, C5a, and TCC of the complement system) for the diagnosis of LC [129].…”
Section: Discussionmentioning
confidence: 99%
“…Further, we observed significant decreases of levels for some proteins of the complement cascade amongst the COVID-19 convalescents (Figure 5) contrasting observations from the acute phase 68,69 ( Table 1C ). The complement system is also known for a complex relationship with long COVID 70 : complement dysregulation might even be predictive of long COVID 71 . The complement cascade directly associates with altered blood coagulation in COVID-19 pathology 20,72,73 , and blood coagulation, which in turn involves platelet activation.…”
Section: Discussionmentioning
confidence: 99%